DNA-binding studies of valrubicin as a chemotherapy drug using spectroscopy and electrochemical techniques - Reza Hajian; Parvin Hossaini; Zahra Mehrayin; Pei Meng Woi; Nafiseh Shams (Elsevier, 2017)
In this study, the molecular interactions between valrubicin, an anticancer drug, and fish sperm DNA have been studied in phosphate buffer solution (pH 7.4) using UV-Vis spectrophotometry and cyclic voltammetry techniques. Valrubicin intercalated into double stranded DNA under a weak displacement reaction with methylene blue (MB) molecule in a competitive reaction. The binding constant (kb) of valrubicin-DNA was determined as 1.75×103 L/mol by spectrophotometric titration. The value of non-electrostatic binding constant (kt0) was almost constant at different ionic strengths while the ratio of kt0/kb increased from 4.51% to 23.77%. These results indicate that valrubicin binds to ds-DNA via electrostatic and intercalation modes. Thermodynamic parameters including ΔH0, ΔS0 and ΔG0 for valrubicin-DNA interaction were determined as −25.21×103 kJ/mol, 1.55×102 kJ/mol K and −22.03 kJ/mol, respectively. Cyclic voltammetry study shows a pair of redox peaks for valrubicin at 0.45 V and 0.36 V (vs. Ag/AgCl). The peak currents decreased and peak positions shifted to positive direction in the presence of DNA, showing intercalation mechanism due to the variation in formal potential.